Formula optimization of sustained-release ibuprofen tablet using simplex lattice design with mixture of caragenan, calsium sulphate, and PVP-K30 - Wuryanto Hadinugroho; Achmad Fudholi (Indonesian Journal of Pharmacy, 2011)
Ibuprofen is one of non steroid anti inflammatory drug (NSAID), derivated propionic  acid  often  use  rheumatoid  therapy.  Frequented  using  can  make unpleasant  of  patient,  solution  for  this  problem  by  sustained  release  ibuprofen tablet design. This experiment aim is find out the optimized formula of sustained release  ibuprofen  tablet  with  hardness  of  ≥  4  kgf,  brittleness  of  ≤  1  %,  and 0.7-0.9 mg/minutes ibuprofen rate out by using mixture of carrageenan, calcium sulphate  and  PVP-K30.  This  formula  use  ibuprofen  as  400  mg,  the  mixture  of carrageenan, calcium sulphate and  PVP-K30  as  12 mg,  so  tablet total  weight  is 600  mg,  the  mixture  total  weight  is.  The  proportion  was  optimized  by  using simplex  lattice  design  special  cubic  model.  There  are  seven  formula  in  this design  (each  three  formula  consist  of  100  %,  three  formula  consists  of  two  as 50 % : 50 % and last formula mixture three component as 33.33 % of each) to get  coefficient  of  equation  Y  =  a(A)+b(B)+c(C)+ab(A)(B)+ac(A)(C)+bc(B)(C)+ abc(A)(B)(C).  Based  of  each  optimized  parameter  equation  is  got  contour  plot and  combined  to  superimposed  contour  plot,  so  the  optimized  formula  can  be found.  Based  of  superimposed  contour  plot  is  mixture  carrageenan:calcium sulphate:PVP-K30 comperation of optimized formula sustained release ibuprofen tablet are  0.347  :  0.233  :  0.420  to  find out  the optimized  formula  of sustained release  ibuprofen  tablet  with  the  hardness  as  5.71;  brittleness  as  0.28;  and ibuprofen  rate  out  as  0.79.  The  most  dominant  increase  factor  on  hardness  is calcium sulphate, on brittleness is carrageenan and on ibuprofen rate out is PVPK30.  About  interaction,  the  most  hardness  is  calcium  sulphate-PVP-K30,  the most  brittleness  and  ibuprofen  rate  out  is  carrageenan-calcium  sulphate-PVPK30.Key words:carrageenan, calcium sulphate, PVP-K30, ibuprofen.